European banking integration: is foreign ownership affecting banking efficiency? - Gallizo, José Luis; Moreno, Jordi; Salvador, Manuel (Journal of Business Economics and Management, 2014)
The aim of this study is to analyze how European integration and, especially, changes in ownership, has affected banking efficiency in Central and Eastern European countries which have recently experimented this process more intensely. Using a stochastic frontier approach, applied to panel data, we have estimated bank efficiency levels in a sample of 189 banks from 12 countries during the period 2000 to 2008 and we have analyzed the influence of some bank characteristics on these efficiency levels. The results show that European integration has significantly improved the cost efficiency of banks in these countries, but profit efficiency has significantly decreased. We have found very small differences between different ownership types and only a very small impact of foreign ownership on cost efficiency, showing that the entry of foreign ownership is not enough to explain the significant variations in banking efficiency after the accession.